STRUKTUR KALIMAT DAN DIKSI TEKS EKSPOSISI KARYA SISWA KELAS VIII SMP NEGERI 12 PADANG - Yodeska, Yolla Karchia; Nursaid, Nursaid (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2019)
ABSTRACT This research was conducted to describe sentence structure and diction (word selection) exposition text of class VIII students of SMP Negeri 12 Padang. This type of research is qualitative with descriptive method. The data of this study are qualitative data in the form of text exposition of students. Data are analyzed by steps, namely (1) the researcher identifies the sentence structure contained in the students' exposition text, (2) the researcher identifies the diction contained in the student's exposition text, (3) the results of the analysis by the triangulation informant, (4) make conclusions. Based on the results of the study, two things are summarized as follows. First, in writing about the exposition text of the eighth grade students of Padang 12 Middle School using six basic sentence patterns. The sixth basic pattern of the exposition text sentence structure is SP, SPO, SPPel, SPK, SPOK, and SPOPel. This is evident from the 40 exposition texts that have been analyzed, the basic pattern of the sentence most used by students is SPOPel, while the basic pattern of the least used sentence is SP. Second, when viewed from the use of diction with the accuracy of the use of diction 90% and the use of 10% diction which is inaccurate in the exposition text by class VIII students of Padang Middle School 12. Kata Kunci: Stuktur Kalimat, Diksi, dan Teks Eksposisi